Two-year observation of a young woman with recurrent myocardial infarction - M. S. Freydlina; A. N. Kharlamov; Ya. L. Gabinsky; E. D. Rozhdestvenskaya; O. S. Novoselova; V. V. Altukhov; T. A. Naydanova; L. A. Shardina; S. D. Chernyshev (Кардиоваскулярная терапия и профилактика, 2005)
The article is devoted to a clinical case of recurrent acute myocardial infarction (AMI) in a 35-year-old woman. The patient had several AMI risk factors (RF): long-term, intensive smoking, Chlamydia pneumoniae and Helicobacter pylori infections, medical abortions, dysmenorrhea, uterine myoma, hormonal and hemostatic dysbalance, and psycho-emotional stress. Endothelial dysfunction, pediatric anamnesis, and multiple organ pathology also played their roles in recurrent AMI pathogenesis.